Multi-channel support for data-gathering trees in wireless sensor networks - Alfraihat, Wasan Ahmad Sulieman (2010)
In traditional applications of Wireless Sensor Networks (WSNs), energy efficiency may be considered to be the most important concern whereas utilizing the bandwidth and maximizing the throughput are of secondary importance. However, recent applications, such as structural health monitoring, require high amounts of data to be collected at a faster rate. Furthermore, it is possible to have multiple applications running on the same network, especially with some operating systems for WSNs. This certainly leads to larger amounts of data to be transmitted in the network and handling the traffic. In general, multi-channel scheme is widely used in wireless networks, to reduce the interference and to increase the throughput. Although that current radios support up to 16 channels, this is not enough to allow all of the nodes which are in the same interference range to transmit concurrently especially in dense networks. A new multi-channel duty cycle protocol, known as Adaptive Fast Convergecast MAC (AFC-MAC), is proposed especially for data gathering tree which combines the staggered wake up schedule with the multi-channel approach to reduce the number of competing nodes in order to get a transmission. AFC-MAC composed of two phases, the channel assignment phase and the adaptive scheduling phase. The channels are assigned to the nodes in a way to allow the nodes to send the data packets with a minimum delay by eliminating the interference with the concurrent transmissions of the next nodes along the path, and at the same time the nodes consider the impact of the adjacent channels in the channel assignment decision. This interference elimination helps the nodes to schedule the next active time-slots time cycle with a minimum delay to adapt to the network’s high traffic rate. The two-way data forwarding is supported by the adaptive schedule phase by adopting a special synchronization mechanism to avoid the contradiction with the sink’s reports forwarding. One of the multi-channel duty cycle protocols, Path-Oriented Real Time MAC protocol (PR-MAC) is examined and simulated using the ns2 simulation environment. AFC-MAC is compared with PR-MAC in terms of Aggregate MAC throughput, delivery ratio, and energy efficiency. Since AFC-MAC assigns the channels to nodes rather than paths, the convergecast speed and the throughput has been enhanced. Specifically, the throughput is enhanced 4.784 times to the achieved throughput in PR-MAC, and the delivery ratio in AFC-MAC has been enhanced 2.242 times compared to PR-MAC.